Modified Guizhi Shaoyao Zhimu Decoction in the treatment of gout: A systematic review and meta-analysis - Hao Liu; Xiansu Chi; Hongxiu Zhang; Huishan Shi; Jin Pan; Yong Wang; Xiaoyan Xue; Yangting Lu; Xiaobin Song; Ke Ma (Elsevier, 2022)
Background: Gout is a common joint disease. Currently, although the clinical application of Guizhi Shaoyao Zhimu Decoction (GSZD) for the treatment of gout has a good effect, there is still limited literature focusing on the effectiveness and safety of Guizhi Shaoyao Zhimu Decoction. Purpose: Meta-analysis was conducted to analyze randomized controlled trials (RCTs) to determine the effectiveness and safety of GSZD for the treatment of gout. Methods: The published research papers involving RCTs of GSZD treating gout were searched in the literature databases from inception to March 2022. RCTs meeting the inclusion criteria was include and assessed. RevMan 5.3, Stata 15.1 and TSA 0.9.5.10 Beta software were applied for statistical analysis. Results: Twenty-two RCTs involving 1800 patients with gouty arthritis were systematically reviewed. The curative effect of the Chinese medicinal group was better than that of the control group [OR= 3.33, 95% CI (2.46, 4.51), P<0.00001]. Meanwhile, the incidence of adverse reactions was lower in the treatment group [OR= 0.34, 95% CI (0.19, 0.61), P = 0.0003]. Besides, modified GSZD or modified GSZD combined with western medicine or combined with nursing of Traditional Chinese Medicine group significantly decreased the levels of C-reactive protein [MD = -3.32, 95% CI (-4.97, -1.47), P< 0.00001] and erythrocyte sedimentation rate [MD = -4.80, 95% CI (-7.37, -2.24), P = 0.0002]. Conclusion: The current research results showed that the single application of GSZD and the combined application of modified GSZD and other treatments were better than the single application of western medicine or Chinese patent medicine.